(untitled) (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
Sport is a dynamic and fast-growing industry, based on a competitive physical activity or game and complex social activity. The growth of the sports industry has a direct impact on the employment, given its labor-intensive character, but also a positive impact on the quality of life and public health. Some estimates show that the global sports market is growing at a compound annual growth rate of over 5%, and despite the global Covid-19 pandemic crisis, it is estimated that by 2025 it will reach a value of almost 600 billion dollars, or 826 billion dollars by 2030. Given the complexity of sports functions and huge amounts invested in professional sports, the problem of financing projects in sports requires the involvement of the entire community. The method of financing sports projects and activities depends primarily, on the level of development of a specific economy, financial market development, whereby various internal and external sources of financing are available. Sources of income from sports activities are most often membership, sales of ticket and other props of sports club, sponsorships of large and rich companies, selling rights to a sports event, including the rights of TV broadcasts. Different national and regional support programs are also a legitimate source of funding. In somewhat more developed countries, sports activities and clubs are financed in capital markets or through crowdfunding, especially popular method recently, which can raise money through relatively small contributions from a large number of donors, bypassing traditional financing sources, financial intermediaries, strict borrowing conditions and procedures. Although the concept of social financing has long been present, crowdfunding has become a popular and important way of raising funds after the 2008 global crisis, when entrepreneurs found it difficult to access bank loans and other financing sources. However, crowdfunding reaches its full potential with the Internet and social networks development, which contributed to the international networking of project creators and their potential donors, efficient campaigns creation and greater projects visibility. Sports projects can be financed through any crowdfunding platform, it they meet the criteria. There are more than 600 crowdfunding platforms in the world and only few specialized sports financing. In this paper, we will present the theoretical settings of crowdfunding, including definition, perspectives and types. Based on the content analysis and case study of funding through SportFunder, specialized sports crowdfunding platform, we will present that there is significant potential for financing sports projects through crowdfunding, but that the success of each campaign depends on many factors, primarily territorial, political and cultural. On the other hand, the positive outcome of funding will depend on the quality of the project and its campaign organization and promotion.